Integrated Model of Problem Structuring and Multicriteria Group Decision Making for Social Sustainable Development - Morais, Danielle Costa; De Almeida, Adiel Teixeira (Brazilian Journal of Operations & Production Management, 2010)
Many social decisions in the real world are characterized by deep complexity, not only in terms of economic aspects, but also dealing with sustainability policy problems. Indeed, the emphasis to find a solution by representing the situation and its relationships in a decision problem only mathematically, focused simply in restricts views, is not enough. Nowadays, to make a social decision is imperative to promote a group discussion to find a sustainable solution and to input more emotional arguments into the problem. However, although there are several methods of problem structuring (soft OR) and methods to evaluate the problem (hard OR), there are still few works dealing with the integration of these two approaches. This paper proposes a group decision model, integrating tools of problem structuring and multicriteria evaluation. The problem structuring approach is used to facilitate and to share information starting from the participative development, as a way to generate alternative ideas of solution and to improve the learning process among all the involved members. The multicriteria evaluation is used to find a global solution for the problem, incorporating the points of view of all members involved in the decision process. The purpose of this model is to generate a richer and more effective way of handling the problem situation.